2021
DOI: 10.3389/fcell.2021.741060
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Mechanosensitive Piezo1 Alleviated Renal Fibrosis Through p38MAPK-YAP Pathway

Abstract: Renal fibrosis is the most common pathological manifestation of a wide variety of chronic kidney disease. Increased extracellular matrix (ECM) secretion and enhanced microenvironment stiffening aggravate the progression of renal fibrosis. However, the related mechanisms remain unclear. Here, we evaluated the mechanism by which ECM stiffness aggravates renal fibrosis. In the present study, renal mesangial cells (MCs) were cultured on polyacrylamide hydrogels with different stiffness accurately detected by atomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 44 publications
2
27
0
Order By: Relevance
“…As discussed for tumor cases and as already proposed for renal tumors [ 21 , 121 , 149 ], Piezo1 could also be, at least, a biomarker for discriminating the aggressiveness of cardiac fibrosis and, at most, a beneficial therapeutic target. Moreover, the possibility of restoring its physiological activity may interrupt the positive feedback in which its increased activity promotes ECM remodeling in a way in which its stiffness-induced stimulated activity is again enhanced.…”
Section: Discussionmentioning
confidence: 87%
“…As discussed for tumor cases and as already proposed for renal tumors [ 21 , 121 , 149 ], Piezo1 could also be, at least, a biomarker for discriminating the aggressiveness of cardiac fibrosis and, at most, a beneficial therapeutic target. Moreover, the possibility of restoring its physiological activity may interrupt the positive feedback in which its increased activity promotes ECM remodeling in a way in which its stiffness-induced stimulated activity is again enhanced.…”
Section: Discussionmentioning
confidence: 87%
“…Mechanosensors in mesangial cells remained unidentified for a long time. Quite recently, Fu et al 38 reported that Piezo1 is involved in ECM gene expression in cultured mesangial cells under mechanical stress and in renal fibrosis in a mouse model. They used an unconventional method of culturing cells on hydrogel with different stiffness to evaluate the effects of mechanical stress.…”
Section: Discussionmentioning
confidence: 99%
“…In the experiments of Wang et al (2020b) , they found that Piezo1 could perceive mechanical load, and Piezo1 could regulate the expression of type II and type IX collagens by changing the nuclear localization of YAP, thus affecting the osteogenic process. In addition, the expression of Piezo1 increased with the rise of gel stiffness in the external environment ( Sun et al, 2020 ; Fu et al, 2021 ). The related experiments carried out by Sun et al with human umbilical cord mesenchymal stem cells (hUC-MSCs) revealed the interaction among Piezo1, integrin and Ca 2+ .…”
Section: Effects Of Hydrogel Stiffness On Tissue Repairmentioning
confidence: 99%